Determination of Protein Content Protein from various growing places of Pineapple (Ananas comosus Merr.) - komari, Noer; Rahmadi, Adi; Samsul Hadi (JURAGAN - Jurnal Agroteknologi, 2024)
Pineapple is a special plant that has a sweet and sour taste and has various benefits. Based on where the pineapple grows, the taste will vary. The aim of this research is to determine the protein content of pineapple based on where it grows. This research method is to determine Lowry protein levels using spectrophotometry. The results of this research were measurements of protein levels in peat areas, the protein concentration was 48.14 µg/mL. After conversion by dilution, the volume used resulted in a sample weight of 0.019 grams. When converted to a sampling weight of 80 grams, the sample weight in percent is 0.024%. Meanwhile, when measuring in a mountainous environment, a level of 40.99 µg/mL was obtained, this is equivalent to a sample weight of 0.016 grams, when divided by the sampling weight of 80 grams, a level of 0.021% w/w was obtained. When sampling was carried out in the lowlands, the protein level obtained was 45.39 µg/mL. So the protein obtained is 0.018 grams, when you calculate the % weight per weight you get a level of 0.022%. The conclusion of this research is that the highest protein content is pineapple that grows in a peat environment.